Downregulation of Serine Protease HTRA1 Is Associated with Poor Survival in Breast Cancer - Lehner, Anna (Public Library of Science, 2013)
HTRA1 is a highly conserved serine protease which has been implicated in suppression of epithelial-to-mesenchymal-transition (EMT) and cell motility in breast cancer. Its prognostic relevance for breast cancer is unclear so far. Therefore, we evaluated the impact of HTRA1 mRNA expression on patient outcome using a cohort of 131 breast cancer patients as well as a validation cohort including 2809 publically available data sets. Additionally, we aimed at investigating for the presence of promoter hypermethylation as a mechanism for silencing the HTRA1 gene in breast tumors. HTRA1 downregulation was detected in more than 50% of the breast cancer specimens and was associated with higher tumor stage (p = 0.025). By applying Cox proportional hazard models, we observed favorable overall (OS) and disease-free survival (DFS) related to high HTRA1 expression (HR = 0.45 [CI 0.23–0.90], p = 0.023; HR = 0.55 [CI 0.32–0.94], p = 0.028, respectively), with even more pronounced impact in node-positive patients (HR = 0.21 [CI 0.07–0.63], p = 0.006; HR = 0.29 [CI 0.13–0.65], p = 0.002, respectively). Moreover, HTRA1 remained a statistically significant factor predicting DFS among established clinical parameters in the multivariable analysis. Its impact on patient outcome was independently confirmed in the validation set (for relapse-free survival (n = 2809): HR = 0.79 [CI 0.7–0.9], log-rank p = 0.0003; for OS (n = 971): HR = 0.63 [CI 0.48–0.83], log-rank p = 0.0009). In promoter analyses, we in fact detected methylation of HTRA1 in a small subset of breast cancer specimens (two out of a series of 12), and in MCF-7 breast cancer cells which exhibited 22-fold lower HTRA1 mRNA expression levels compared to unmethylated MDA-MB-231 cells. In conclusion, we show that downregulation of HTRA1 is associated with shorter patient survival, particularly in node-positive breast cancer. Since HTRA1 loss was demonstrated to induce EMT and cancer cell invasion, these patients might benefit from demethylating agents or histone deacetylase inhibitors previously reported to lead to HTRA1 upregulation, or from novel small-molecule inhibitors targeting EMT-related processes.